Ensuring The Safe Movement of Vehicles on Mountain Roads - Assistant Professor Eshanbabaev Abror Arslanovich; Assistant Professor Khamzaev Asrorkhon Akmalkhonovich (Genius Publishing Group, 2023)
This article discusses the features of traffic on mountainous sections of roads in the conditions of the Republic of Uzbekistan, analyzes the intensity and composition of traffic flows, features of road conditions, traffic accidents
Keywords: Intensity; road traffic accidents; ascent